AT4 receptor is insulin-regulated membrane aminopeptidase: potential mechanisms of memory enhancement - Albiston, Anthony L; Mustafa, Tomris; McDowall, Sharon G; Mendelsohn, Frederick A.O; Lee, Joohyung; Chai, Siew Yeen (Trends in endocrinology and metabolism, 2003)
Although angiotensin IV (Ang IV) was thought initially to be an inactive product of Ang II degradation, it was subsequently shown that the hexapeptide markedly enhances learning and memory in normal rodents and reverses the memory deficits seen in animal models of amnesia. These central nervous system effects of Ang IV are mediated by binding to a specific site, known as the AT(4) receptor, which is found in appreciable levels throughout the brain and is concentrated particularly in regions involved in cognition. This field of research was redefined by the identification of the AT(4) receptor as the transmembrane enzyme, insulin-regulated membrane aminopeptidase (IRAP). Here, we explore the potential mechanisms by which Ang IV binding to IRAP leads to the facilitation of learning and memory.